Phenotypic miRNA screen identifies miRNA-26b to promote the growth and survival of endothelial cells - Martello, A; Mellis, D; Meloni, M; Howarth, A; Ebner, D; Caporali, A; Zen, A (Nature Publishing Group, 2018)
Endothelial cell proliferation is a crucial event in physiological and pathological angiogenesis. MicroRNAs (miRNAs) have emerged as important modulators of the angiogenic switch. Here, we conducted high content screen of a human miRNA mimic library to identify novel regulators of endothelial cell growth systematically. Several miRNAs were nominated that enhanced or inhibited endothelial cell growth. Out of these, we focused on miR-26b, which is a conserved candidate and expressed in multiple human endothelial cell types. miR-26b overexpression enhances endothelial cell proliferation, migration, and tube formation while inhibition of miR-26b suppressed the proliferative and angiogenic capacity of endothelial cells. A combinatory functional siRNA screening of 48 predicted gene targets revealed that miR-26b enhanced endothelial cell growth and survival through inhibiting PTEN expression. Local administration of miR-26b mimics promoted the growth of new microvessels in the Matrigel plug model. In the mouse model of hindlimb ischemia, miR-26b was found to be downregulated in endothelium in the first week following ischemia, and local overexpression of miR-26b improved the survival of capillaries and muscle fibers in ischemic muscles. Our findings suggest that miR-26b enhances endothelial cell proliferation, survival, and angiogenesis. miR-26b is a potential target for developing novel pro-angiogenic therapeutics in ischemic disease.